2011
DOI: 10.1214/11-ejs600
|View full text |Cite
|
Sign up to set email alerts
|

Kernel regression with functional response

Abstract: We consider kernel regression estimate when both the response variable and the explanatory one are functional. The rates of uniform almost complete convergence are stated as function of the small ball probability of the predictor and as function of the entropy of the set on which uniformity is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 11 publications
0
32
0
3
Order By: Relevance
“…In most of applications in functional regression the explanatory variable is a one dimensional curve (see for instance [20], [21], [12], [16]) and the response is scalar. The nonparametric methodology has been extended and used also to responses being also a one dimensional curve (see eg [11] or [10]), but in the situation depicted in this paper both the explanatory variables (which is a compact two dimensional set) and the response one (which is a bivariate density) are not simple one-dimensional curves. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of applications in functional regression the explanatory variable is a one dimensional curve (see for instance [20], [21], [12], [16]) and the response is scalar. The nonparametric methodology has been extended and used also to responses being also a one dimensional curve (see eg [11] or [10]), but in the situation depicted in this paper both the explanatory variables (which is a compact two dimensional set) and the response one (which is a bivariate density) are not simple one-dimensional curves. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The asymptotic properties of the estimated operatorR h,α can be derived directly from the recent advances obtained in nonparametric regression when both explanatory and response variables are functional (see for instance [11] for asymptotic normality and [10] for uniform rates of convergence). These consistency results are not our purpose here since we wish rather to discuss how this method may allow us to select the probability content α.…”
Section: Theorem 1 Under the Conditions (A4)-(a12) One Hasmentioning
confidence: 99%
See 1 more Smart Citation
“…A kernel regression estimator when both the response and the explanatory variables are functional was also recently considered [21]. Thinking of the explanatory variables being quantitative, such as, daily temperature, daily humidity, daily wind speed, etc., the resulting functional kernel regression approach could be used for STLF.…”
Section: A Existing Approachesmentioning
confidence: 99%
“…Extend to nonparametric functional regression model with functional responses (see for example, Ferraty et al, 2011Ferraty et al, , 2012 As a sequel of the simulation study, we also investigate the MSE and MISE of five other error densities, as shown in Tables (.6) and (.7). The first four error densities are simulated from mixtures of Gaussian densities selected from Marron and Wand (1992), while the last one is simulated from a non-Gaussian error density.…”
Section: Conclusion and Some Open Questionsmentioning
confidence: 99%